Question

# If $$x=\displaystyle\frac{\sqrt{5}-\sqrt{3}}{\sqrt{5}+\sqrt{3}}$$ and $$y=\displaystyle\frac{\sqrt{5}+\sqrt{3}}{\sqrt{5}-\sqrt{3}}$$ , find the value of $${x}^{2}+{y}^{2}-6xy$$.

Solution

## Given that$$x= \dfrac{\sqrt5 - \sqrt3}{\sqrt5 +\sqrt3}$$$$= \dfrac{(\sqrt5 - \sqrt3)(\sqrt5-\sqrt3)}{(\sqrt5 +\sqrt3)(\sqrt5-\sqrt3)}$$$$= \dfrac{8-2\sqrt{15} }{2}$$$$x= 4-\sqrt{15}$$$$x^2= 31-8\sqrt{15}$$  .....................................(1)$$y= \dfrac{\sqrt5 + \sqrt3}{\sqrt5 -\sqrt3}$$$$= \dfrac{(\sqrt5 + \sqrt3)(\sqrt5+\sqrt3)}{(\sqrt5 +\sqrt3)(\sqrt5-\sqrt3)}$$$$= \dfrac{8+2\sqrt{15} }{2}$$$$y= 4+\sqrt{15}$$$$y^2= 31+8\sqrt{15}$$  .....................................(2)$$xy= [4 - \sqrt{15}] \times [4 +\sqrt{15}]$$$$\Rightarrow xy= 1$$  ........................................(3)Now we have to find out the value of given expression$$x^{2}+y^2 -6xy = (31-8\sqrt{15})+(31+8\sqrt{15})-6$$                          $$=62-6 =56$$Hence, $$56$$ is the answerMathematics

Suggest Corrections

0

Similar questions
View More

People also searched for
View More